Komunikasi Politik Digital Sayap Partai di Indonesia dalam Penguatan Kaderisasi Partai - Raymundus Anthony Samadi; Andi Faisal Bakti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The transformation of political communication in the digital era has fundamentally altered the ways political parties and their affiliated wing organizations interact with party cadres and the broader public. In Indonesia, party wing organizations such as Angkatan Muda Pembaharuan Indonesia (AMPI), Angkatan Muda Partai Golkar (AMPG), and other youth wings increasingly rely on social media as the primary medium for political cadre formation. However, this shift has not only created new opportunities for participation but has also generated structural problems, including the dominance of symbolic communication, the personalization of political elites, and the subordination of ideological discourse to the algorithmic logic of digital platforms. This article aims to critically examine how the digital political communication of party wing organizations operates within the context of Indonesia’s representative democracy, the extent to which it constitutes a deliberative public sphere for young cadres, and how such practices affect the quality of political cadre formation. Employing a critical paradigm and a transdisciplinary qualitative approach, the study integrates Habermas’s theory of the public sphere, Aeron Davis’s evaluation of democratic communication, and the concept of the mediatization of politics. The findings indicate that the digital communication of party wings tends to function primarily as an instrument of symbolic consolidation and loyalty mobilization rather than as an arena for dialogical political education. Consequently, digital cadre formation produces representational identities more than critical political consciousness. This article therefore recommends a reorientation of the digital political communication of party wing organizations toward deliberative and emancipatory models in order to strengthen internal party democracy and promote substantive political regeneration.